Clinical management and gross pathological findings of a severe anaplamosis in a dairy cow - Abba, Yusuf; Abdullah, Faez Firdaus Jesse; Sadiq, Muhammed Abubakar; Ibrahim, Hayder Hamzah; Lim, Eric Teik Chung; Bitrus, Asinamai Athliamai; Mohd Lila, Mohd Azmi; Hambali, Idris Umar (Network for the Veterinarians of Bangladesh, 2016)
Objectives: Bovine anaplasmosis is an arthropod-borne hemolytic disease of cattle which is caused by a rickettsia; Anaplasma marginale. Anaplasmosis is also called "Yellow bag" or yellow fever, where the affected animals usually develop a jaundiced appearance. The objective of this study was to investigate the clinical findings, treatment and gross pathology of a severe anaplasmosis in a dairy cow. Materials and methods: In this report, a rare case of fatal anaplasmosis in a 4 year old Jersey-Friesian cow, weighing about 200 kg was reported. Diagnosis was done based on clinical symptoms, blood examination for the presence of A. marginale, and biochemical analyses of blood. Leishman staining was done to check the A. marginale at the margin of erythrocytes. Treatment was instituted with blood transfusion and Oxytetracyline dosed at 20 mg/kg body weight and iron supplement containing 20 mL Cobaphos (containing Phosphorus 125mg + Cyanocobalamine 0.05 mg) and 20 mL Fercobsang containing Iron (as ammonium citrate) 1.75 mg, Cyanocobalamine (Vitamin B12) 0.025 mg, Nicotinamide (vitamin PP) 20 mg, Cobalt (as digluconate) 0.0067 mg, Benzyl Alcohol (E1519) 20.8 mg) were given intramuscularly. Results: The cow did not survive the infection as it eventually died of the disease. Post mortem examination showed gross evidence of splenomegaly, hepatomegaly, distended bile duct and generalized jaundice. Conclusion: Based on the consequence of this case report, preventive vector control, prompt and appropriate treatment and improved management practices are recommended in order to prevent clinical anaplasmosis cases among cattle.